2009
DOI: 10.1038/cdd.2009.57
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of guanylyl cyclase (β1 subunit) expression impairs neurite outgrowth and synapse maturation in cultured cerebellar granule cells

Abstract: The increased expression of different soluble guanylyl cyclase (sGC) subunits during development is consistent with these proteins participating in the formation and establishment of interneuronal contacts. Functional sGC is generated by the dimerization of an a-subunit (sGCa1/2) with the b1-subunit (sGCb1), and both depletion of the sGCb1 subunit and inhibiting sGC activity impair neurite outgrowth. Similarly, impairing sGC activity diminishes the amount of growth-associated protein (GAP-43) and synapsin I, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(28 citation statements)
references
References 46 publications
1
27
0
Order By: Relevance
“…Other studies already suggested a link between Gap43 mRNA levels and NO signaling due to co-induction of nNos and Gap43 during axon regeneration and reactive synaptogenesis following injury of spinal motoneurons [49] and sensory neurons [50]. Furthermore, a downregulation of Gap43 was reported after silencing of soluble guanylate cyclase subunits, the central elements of cGMP-mediated NO signaling [51]. Finally, the present study demonstrates Gap43 downregulation to be a consequence of NO withdrawal in neuronal progenitors and MB cells.…”
Section: Discussionsupporting
confidence: 78%
“…Other studies already suggested a link between Gap43 mRNA levels and NO signaling due to co-induction of nNos and Gap43 during axon regeneration and reactive synaptogenesis following injury of spinal motoneurons [49] and sensory neurons [50]. Furthermore, a downregulation of Gap43 was reported after silencing of soluble guanylate cyclase subunits, the central elements of cGMP-mediated NO signaling [51]. Finally, the present study demonstrates Gap43 downregulation to be a consequence of NO withdrawal in neuronal progenitors and MB cells.…”
Section: Discussionsupporting
confidence: 78%
“…The cell suspension was electroporated with Amaxa™ Nucleofector II using Rat Neuron Amaxa Nucleofector Kit (Lonza), following the instructions provided by the manufacturer (programme O-03) as described [34]. For transfection, 1 µg of VGLUT1-pHluorin (VGpH) DNA [27] was used per 5×10 6 cells and the cells were finally seeded at a density of 1.6×10 6 cells/coverslip.…”
Section: Methodsmentioning
confidence: 99%
“…In this sense, both 8-Br-cGMP and NMDA induce an increase in the density of synapsin puncta [30] and GluA1 clusters, effects that are counteracted and reversed by KT5823. The increase in cluster density was accompanied by an increase in immunofluorescence intensity compatible with the presence of more protein in these clusters, while conversely, the reduced cluster density provoked by exposure to KT5823 was accompanied by a reduction in their mean fluorescence.…”
Section: Discussionmentioning
confidence: 99%
“…In culture, cerebellar granule cells establish synapses with themselves and their development is also affected by the NO and cGMP pathway. While NO negatively regulates precursor proliferation through a cGMP-independent mechanism [65], it also triggers differentiation and maturation by a cGMP-dependent one [30,31,66]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation